Congenital tuberculosis: a case report (NIGERIAN JOURNAL OF PAEDIATRICS, 2024)
Abstract: Congenital tuberculosis is insufficiently understood and has been rarely reported even in areas endemic for the disease. Unless a high index of suspicion is maintained, the diagnosis can be missed. A case of congenital tuberculosis is herein reported to illustrate the difficulty in identifying such infants and also to sensitize the medical practionner in TB endemic areas of the need foretiologic diagnosis in congenital pneumonias as well as for antenatal screening forTBin mothers at risk.